Identifikasi Jamur Pityrosporum Ovale Penyebab Penyakit Pityriasis Capitis Pada Pasukan Pengibar Bendera (Paskibra) SMA “X” Kota Tangerang - Afandi Putra Yuda; Seftiwan Pratami Djasfar (Jurnal Ventilator, 2023)
Pityriasis capitis (dandruff) is a scalp disorder characterized by white scales and itching which causes a dilemma for sufferers because it can reduce appearance or attractiveness and cause a student to lack self-confidence. Pityriasis capitis (dandruff) is experienced by all groups, from children, teenagers to the elderly, of all genders. Paskibra members are an example of teenagers who often do outdoor activities. This research aims to identify the fungus Pityrosporum ovale which causes dandruff in Paskibra members. The research design used was descriptive observational, where the main aim was to obtain an overview of the Pytorosporum ovale fungus on the scalp of Paskibra SMA “X” Tangerang City and the sample of this study were 19 Paskibra members. The repair materials were scalp scrapings on dandruff sufferers to do microscopic examination with 10% KOH and Lactophenol Cotton Blue then followed by culture on Sabouraud Dextrose Agar with chloramphenicol at 37OC for 2-5 days. The results of the research on 19 respondents conducted at SMA “X” Tangerang City showed that 18 respondents (95%) were positively infected with the fungus Pityrosporum ovale and 1 respondent (5%) was negatively infected with dandruff. Macroscopically Pityrosporum ovale has a morphological form that is white in color and fine textured and microscopically has morphological characteristics of microconidia oval and budding.